Joint time-frequency analysis of ammunition velocity doppler radar signals - Ong, Soon Huat. (2008)
Today's state-of-the-art ammunition Doppler radars use the Fourier spectrogram for the time-frequency representation of Doppler signals, even though many new distributions have been developed. This thesis evaluates and compares the linear time- frequency representations, the quadratic time-frequency representations, and the wavelet packet transform for the joint time-frequency analysis of ammunition Doppler signals. In the linear time-frequency representations, a Doppler signal is decomposed into time- frequency or time-scale atoms. The Gabor representation, the short-time Fourier transform and the continuous wavelet transform are members of this class of representations. The quadratic time-frequency representations considered are the Fourier spectrogram, the Wigner distribution, the Choi-Williams distribution and the Cone-kernel distribution.